Quantifying the Importance of Nationality in Determining International Protection Outcomes in Ireland - Keogh, Gerard (The Economic and Social Review, 2016)
We examine 40,434 International Protection (IP) determinations for non-EEA nationals covering a 16-year period in Ireland. We quantify the weight of importance of nationality versus process factors (e.g. length of time awaiting a decision) and applicant (e.g. gender) related characteristics in determining the IP outcome and show that nationality accounts for over twothirds of the explained variation in outcomes. We also show that a grant of protection of depends on just seven statistically significant applicant characteristics or process factors suggesting the determining officer’s assessment of the credibility of an asylum claim is nuanced. Taken with the fact that the UNHCR provides oversight of the IP determination procedure we take the view that the procedure is reasonably fair. Nonetheless, our analysis also shows that a stiffer determination regime has been in place in Ireland from 2007 to 2013. Our findings have important policy implications for IP in Ireland and elsewhere.